Malaysia’s pivot: navigating Trump’s return for growth and stability - Sharofiddin, Ashurov; Syed Azman, Syed Marwan Mujahid (Malay Mail, 2024)
DECEMBER 3 — The 45th US President, Donald Trump, is set to return to the White House as the 47th President following his victory in the recent US presidential election. Countries across Asia including Malaysia, are recalibrating their economic and strategic approaches. With the possibility of significant changes in U.S. policy on trade and security, Malaysia stands at a crossroads. How can the country leverage its strengths to navigate potential disruptions while positioning itself to benefit economically, socially, and on the global stage?